Serum serotonin levels are elevated in patients with increased risk of rheumatoid arthritis - Wirestam, Lina; Martinsson, Klara; Kastbom, Alf (Frontiers in Medicine, 2023)
Background Even though serotonin (5-HT) has been ascribed immunomodulatory features, very little is known about its role in chronic inflammatory diseases. Serotonin is implicated in inflammation and increased levels have been associated with progression of bone erosions in RA. Objective To investigate serum serotonin levels in patients with increased risk of rheumatoid arthritis (RA) and patients with recent-onset disease. Moreover, we aimed to determine the prognostic value of serotonin for arthritis development and the disease course. Methods Two prospective observational patient cohorts were studied; anti-citrullinated protein antibody (ACPA) -positive patients with musculoskeletal pain without clinical arthritis (n = 82) and patients with early RA (n = 412). Serotonin levels were measured by enzyme-linked immunosorbent assay (ELISA) in baseline serum samples from both cohorts, and longitudinally in at-risk individuals. Results Compared to healthy controls (median 65 ng/ml), serotonin levels were significantly higher in both at-risk individuals (median 111 ng/ml, p < 0.0001) and patients with early RA (median 135 ng/ml, p < 0.0001). No significant differences were found between at-risk individuals and patients with early RA. At-risk individuals progressing to arthritis had similar levels as those not progressing, and no significant differences were seen over time. Baseline levels in early RA did not associate with mean 28-joint disease activity scores during 3 years follow-up. Conclusion Serum serotonin levels are elevated both at, and prior to, onset of RA. However, increased serotonin is not prognostic for arthritis development or disease course.